Challenges of improving treatment outcomes for colorectal and anal cancers in Japan: the Colorectal Cancer Study Group (CCSG) of the Japan Clinical Oncology Group (JCOG). (2nd March 2020) - Ouchi, Akira; Shida, Dai; Hamaguchi, Tetsuya; Takashima, Atsuo; Ito, Yoshinori; Ueno, Hideki; Ishiguro, Megumi; Takii, Yasumasa; Ikeda, Satoshi; Ohue, Masayuki; Fujita, Shin; Shiozawa, Manabu; et al.
Abstract: Colorectal cancer is a major public health concern in Japan. While early-stage colorectal adenocarcinoma treatment entails radical resection of the primary tumor, the importance of perioperative treatment is growing as physicians seek to further improve treatment outcomes. For anal squamous cell carcinoma, definitive chemoradiotherapy is superior to radical surgery in terms of improved patient quality of life. The Colorectal Cancer Study Group of the Japanese Clinical Oncology Group was established in 2001 and has worked to provide answers to common clinical questions and improve treatment outcomes for colorectal and anal cancers through 15 large-scale prospective clinical trials. Here, we discuss the current state of perioperative treatment for early-stage colon, rectal and anal cancers in Japan and approaches taken by the Colorectal Cancer Study Group/the Japanese Clinical Oncology Group to improve treatment outcomes for these cancers. Abstract : The CCSG/JCOG has worked to improve treatment outcomes for colorectal and anal cancers in Japan. Here, we describe the CCSG/JCOG approaches to improve treatment outcomes for these cancers.